P6_1 Bart the Daredevil - Phelan, Joe; Campbell, James; Warne, Ben; Alam, Afrida (Physics Special Topics, 2016)
<!–StartFragment–>This paper examines the feasibility of a planned attempt by Bart Simpson to jump Springfield Gorge on a skateboard. In order to clear the gorge, we have calculated that Bart would need to reach a speed of 22± 4.3ms^-1. In order to reach this speed we estimate the drop-in to Springfield Gorge would require an angle of descent > 50 degrees.<!–EndFragment–>